# Solve for y (y-6)-(y+6)=8y

(y-6)-(y+6)=8y
Simplify (y-6)-(y+6).
Simplify each term.
Apply the distributive property.
y-6-y-1⋅6=8y
Multiply -1 by 6.
y-6-y-6=8y
y-6-y-6=8y
Combine the opposite terms in y-6-y-6.
Subtract y from y.
0-6-6=8y
Subtract 6 from 0.
-6-6=8y
-6-6=8y
Subtract 6 from -6.
-12=8y
-12=8y
-12=8y
Since y is on the right side of the equation, switch the sides so it is on the left side of the equation.
8y=-12
Divide each term by 8 and simplify.
Divide each term in 8y=-12 by 8.
8y8=-128
Cancel the common factor of 8.
Cancel the common factor.
8y8=-128
Divide y by 1.
y=-128
y=-128
Simplify -128.
Cancel the common factor of -12 and 8.
Factor 4 out of -12.
y=4(-3)8
Cancel the common factors.
Factor 4 out of 8.
y=4⋅-34⋅2
Cancel the common factor.
y=4⋅-34⋅2
Rewrite the expression.
y=-32
y=-32
y=-32
Move the negative in front of the fraction.
y=-32
y=-32
y=-32
The result can be shown in multiple forms.
Exact Form:
y=-32
Decimal Form:
y=-1.5
Mixed Number Form:
y=-112
Solve for y (y-6)-(y+6)=8y

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top